Aplicativo para Gerenciamento da Captação domiciliar do Leite Humano - Muri, Lucimar Andrade Cardoso (2020)
Introduction: The human milk bank is a specialized service responsible for the promotion, protection and support to breastfeeding through the clinical assistance for women with issues in breastfeeding, the collection of donated human milk, the pasteurizat